1961
DOI: 10.1001/archpedi.1961.02080010212010
|View full text |Cite
|
Sign up to set email alerts
|

Familial Congenital Complete Heart Block

Abstract: In general, the occurrence of congenital heart disease may be considered to be due to genetic factors, environmental factors, or a combination of the two. When an identical defect is found in more than one member of the same family, a genetic etiology is suggested. The medical literature reveals numerous reports of a wide variety of congenital heart lesions occurring in families. Taussig,1 for example, reported on a family in which patent ductus arteriosus appeared in 3 successive generations. This experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Uncommonly there may also be polydactyly of the feet (6). Possibly congenital heart block may be associated with polydactyly (7).…”
mentioning
confidence: 99%
“…Uncommonly there may also be polydactyly of the feet (6). Possibly congenital heart block may be associated with polydactyly (7).…”
mentioning
confidence: 99%
“…Developmental anomalies of the limbs have been reported in associa tion with congenital complete heart block [23]. It should be noted that the second case reported here has such an anomaly of the left upper limb.…”
Section: Discussionmentioning
confidence: 47%
“…The first unequivocal diagnosis of congenital heart block was made by W hite and E ustis in 1928 [34] in a baby whose slow heart rate was detected before birth and was confirmed by electrocardiography soon after birth. Familial occurrence of congenital CHB with electrocardio graphic confirmation was reported by A itken [1], W endkos and Study [33], Canabal and D ighiero [6], Stephan [30], W right et al [35], Connor et al [8], W allgren and A gorio [32], and Lynch and E ngle [23]. Combrink et al [7] reported varying degrees of right bundle branch block in all four siblings of a family.…”
Section: Discussionmentioning
confidence: 60%